Seperation of the coherence axes on seismograms using the one-dimensional Radon transform - Stankevich, S.A.; Titarenko, O.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
An algorithm for the linear pattern automatic detection on seismograms based on the one-dimensional discrete Radon transform and the flat agglomerative clustering is proposed. The algorithm provides a confidence level acceptable to the seismic exploration. The use of the developed algorithm will improve the automated processing of seismic survey data and enhance the objectivity of their interpretation.